2020
DOI: 10.1186/s12885-020-06748-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic features and genomic analysis of pulmonary blastomatoid carcinosarcoma

Abstract: Background: This study was designed to investigate the clinicopathologic features of pulmonary blastomatoid carcinosarcoma and explore the genomic profiles of epithelial and mesenchymal components in this tumor. Methods: Three cases of pulmonary blastomatoid carcinosarcoma were enrolled in this study. Clinicopathologic information and prognostic data were retrospectively reviewed. Diagnostic immunohistochemistry was performed. The epithelial and mesenchymal components were microdissected to investigate the gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…LRP1B expression is reduced in many cancers, and it is a common mutant gene in human cancers [ 15 17 ]. Among the studies on LRP1B , it was found that LRP1B plays an important role and may serve as a prognostic marker for cancer during the development of various cancers including gastric cancer [ 18 , 19 ]. In addition, the significant associations between LRP1B mutations and TMB in lung cancer and melanoma have also been reported [ 15 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…LRP1B expression is reduced in many cancers, and it is a common mutant gene in human cancers [ 15 17 ]. Among the studies on LRP1B , it was found that LRP1B plays an important role and may serve as a prognostic marker for cancer during the development of various cancers including gastric cancer [ 18 , 19 ]. In addition, the significant associations between LRP1B mutations and TMB in lung cancer and melanoma have also been reported [ 15 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a potential genetic link to pediatric pleuropulmonary blastoma was indicated. Recently, MYCN mutation was detected in the micro dissected mesenchymal component based on capture-based targeted next generation sequencing method ( 14 ). In the index case, we came across a pathogenic mutation in the MYCN and ATM genes on NGS where the latter have not been described in the literature as per our best knowledge.…”
Section: Discussionmentioning
confidence: 99%